The Perspectives of K-12 Stakeholders Involved in Early Implementation of Response to Intervention (RTI) - Kuo, Nai-Cheng (Journal of the American Academy of Special Education Professionals, 2015)
Response to intervention (RTI) is an approach that has been implemented in more than 90% of the states in the U.S. The purpose of the study is to advance understanding of what efforts need to be made in order to increase the likelihood that special education professionals will accept RTI. Data used in this study include individual interviews with two principals, three special education teachers (two of whom were school district RTI coaches), one social worker, and one Title I teacher across four K-12 schools. Data were collected and analyzed around four sets of what qualitative methodologists call "grand tour" questions (Bernard, 2001): (1) respondents’ perceptions about data-based decision making, (2) use of evidence-based interventions at each tier, (3) strengths and challenges to achieving effective coordination, and (4) ongoing supports and professional development needs. The participants’ perspectives offer critical information to advance both research and practices related to RTI.